2012
DOI: 10.1128/aac.06327-11
|View full text |Cite
|
Sign up to set email alerts
|

Strand Length-Dependent Antimicrobial Activity and Membrane-Active Mechanism of Arginine- and Valine-Rich β-Hairpin-Like Antimicrobial Peptides

Abstract: bAntimicrobial peptides with amphipathic ␤-hairpin-like structures have potent antimicrobial properties and low cytotoxicity. The effect of VR or RV motifs on ␤-hairpin-like antimicrobial peptides has not been investigated. In this study, a series of ␤-hairpin-like peptides, Ac-C(VR) n D PG (RV) n C-NH 2 (n ‫؍‬ 1, 2, 3, 4, or 5), were synthesized, and the effect of chain length on antimicrobial activity was evaluated. The antimicrobial activity of the peptides initially increased and then decreased with chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 47 publications
7
107
0
1
Order By: Relevance
“…Based on these lines of evidence, the relationship between peptide length and antimicrobial potency is not linear, and there seems to be a threshold effect. As observed in this study, the antibacterial activity of the trpzip peptides initially increased and then decreased with increasing strand length, which was in agreement with our previous studies on β-sheet peptides (Dong et al 2012). The observed increase in antimicrobial activity with chain length may be attributable to increases in the hydrophobicity and cationicity (Table 1), which are features required for killing bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on these lines of evidence, the relationship between peptide length and antimicrobial potency is not linear, and there seems to be a threshold effect. As observed in this study, the antibacterial activity of the trpzip peptides initially increased and then decreased with increasing strand length, which was in agreement with our previous studies on β-sheet peptides (Dong et al 2012). The observed increase in antimicrobial activity with chain length may be attributable to increases in the hydrophobicity and cationicity (Table 1), which are features required for killing bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…The Trp and Lys residues were located at every other position in the strands, resulting in all hydrophobic residues falling on the same face in the folded hairpin, while positively charged residues were located on the opposite face, forming an amphipathic structure. The two strands were connected by a rigid D Pro-Gly turn sequence that stabilizes the type II β-turn and promotes the formation of β-hairpin conformations (Dong et al 2012;Hilario et al 2003). Finally, the peptides were amidated at the C-terminal to improve peptide stabilization and increase net positive charge for enhanced antimicrobial activities (Nguyen et al 2010).…”
Section: Peptide Design and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also found that the appropriate positioning of Trp residue(s) at the hydrophobic-hydrophilic interface of the helical wheel projection could provide an effective strategy to enhance helical stability and also increase the partitioning or penetration of designed AMPs into microbial membrane lipid bilayers with minimal effects on mammalian cell membranes or their mimics at concentrations required for antimicrobial activities [56,58,59]. Although α-helical AMPs represent the most widely investigated class of AMPs, other types of secondary structures such as β-sheets [43,60] and β-hairpin-like AMPs [61,62] have also been designed and evaluated. For instance, our group has recently designed short synthetic linear β-sheet forming peptide amphiphiles comprised of short recurring (X 1 Y 1 X 2 Y 2 ) n -NH 2 sequences, where X 1 and X 2 : hydrophobic residues (Val, Ile, Phe or Trp), Y 1 and Y 2 : cationic residues (Arg or Lys), and n: number of repeat units based on the common occurrence of amphipathic dyads in membrane spanning β-sheets [43,60].…”
Section: Structurementioning
confidence: 99%
“…In another recent example, evaluation of a series of cyclic β-hairpin-like AMPs with a general sequence of Ac-C(VR) n D PG(RV) n C-NH 2 (n = 1-5), which comprise of two antiparallel Val-and Arg-containing β-sheet strands connected by a type II′ β-turn and further stabilized by a disulfide linkage between the N-and C-terminal Cys residues revealed that a 16-mer peptide with the sequence Ac-C(VR) 3 D PG(RV) 3 C-NH 2 (VR3) had the highest selectivity index and that the intraperitoneal (i.p.) administration of 1.25 to 5 mg/kg of VR3 increased the 7 day survival rate of mice intraperitoneally infected with Salmonella enteric serovar Typhimurium [62].…”
Section: Structurementioning
confidence: 99%